Pengaruh Model Pembelajaran Terpadu Tipe Connected Terhadap Hasil Belajar Siswa Kelas 4 Tema 9 Subtema 1 PB 1 Di SDN Brudu - Zumrotus Sholikhah; Desty Dwi Rochmania (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
On average, there are still teachers who still use conventional methods, to use the Connected type integrated learning model, they are still minimal in using it when learning. In this study, researchers wanted to find out whether the Connected Type Integrated learning model could increase the value of student learning outcomes before and after being given treatment and whether it had an effect on student learning outcomes, that was the purpose of this study. This study uses a quantitative method with the type of one-group pretest-posttest design. The subjects of this research are students. Data collection methods are observation, test, and documentation. The results showed that before being given treatment, the average score obtained by students was 55.26 and after receiving treatment, it increased with a result of 91.25. Therefore, tcount > ttable or 15.12 > 2.056 at a significance level of 0.05, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, which means that the application of the connected type of integrated learning model affects student learning outcomes. Based on the results of these studies, it can be concluded that by using the connected type of integrated learning model, student learning outcomes, especially grade 4 students at SDN Brudu have increased.